More than Just a Laughing Matter: A Coding Framework of Humor in Media Entertainment for Tweens and Teens. Issue 3 (2nd July 2020) - van der Wal, Amber; Piotrowski, Jessica Taylor; Fikkers, Karin M.; Valkenburg, Patti M.
ABSTRACT: Despite the crucial role of humor in t(w)eens' media entertainment, we lack a theoretically informed approach to investigate the prevalence and co-occurrence of humor types in such entertainment. Therefore, this study tested a coding framework of humor in t(w)eens' media entertainment by content-analyzing 107 television series (5, 633 scenes) listed by 10- to 14-year-olds as their favorite. Results confirmed ten humor types (aggressive, slapstick, self-defeating, sexual, irreverent, coping, parody, wordplay, incongruity, absurdity) with aggressive humor most often and coping humor least often present (in 87.9% versus 23.4% of series, respectively). Humor types also frequently co-occurred, highlighting the need to revise existing theories.